(untitled) (Educational Knowledge, 2025)
This article focuses on the living conditions and social origin of students awarded scholarships by the Salvadoran state in the degree program of Technician in Tourism Management and Development, taught under the MEGATEC model, in light of the theories of Bourdieu and Passeron, and Vincent Tinto, regarding habitus and academic and social communities, in relation to student persistence and dropout. The social factors influencing students’ decisions are explored, highlighting the challenges they face, as well as the timely role of academic, social, and cultural communities, and the state’s intervention through the provision of full scholarships. The various capitals—cultural, social, and economic—at play are analyzed, revealing the conditions rooted in the students’ social and family origin, as well as the strategies employed to access the institutional capital required to attain a degree. The article also emphasizes the reproduction of symbolic violence and the perpetuation of social reproduction in the educational system, stemming from the students’ living conditions.